Learning Analytics-Based Sociology Learning Orchestration for Self-Regulated Learning, Engagement, And Concept Mastery Among Public Senior High School Students - Suyuti Suyuti; Devi Septiandini; Ike Arriany; Muhammad Ilman Naafi’a (Sakura Digital Nusantara, 2026)
Purpose: This study examined the effectiveness of learning analytics-based sociology learning orchestration in improving students’ self-regulated learning, engagement, and sociological concept mastery, addressing limited empirical integration of learning analytics, teacher orchestration, and sociology outcomes in secondary education. Methods: A quantitative multi-site quasi-experimental design with a pretest-posttest control group structure was implemented in three public senior high schools in Jakarta. The participants were 209 Grade XI students, comprising 105 students in the experimental group and 104 students in the control group. Data were collected using self-regulated learning and engagement questionnaires, a sociological concept mastery test, a treatment implementation observation sheet, and learning analytics logs. Data were analyzed using descriptive statistics, N-Gain, assumption testing, MANCOVA, and effect size interpretation. Findings: The experimental group showed greater improvement than the control group across all measured outcomes. The intervention produced moderate gains, while learning analytics logs indicated active participation in material access, formative quizzes, assignment submission, discussion, and feedback response. MANCOVA confirmed a significant multivariate intervention effect after controlling for pretest scores. Research Implications: Learning analytics can strengthen sociology learning when teachers use student data to provide timely feedback, identify learning difficulties, and design adaptive pedagogical interventions. Originality: This study contributes to data-informed pedagogy by positioning teachers as learning orchestrators who transform analytics data into adaptive instructional decisions in secondary sociology classrooms.